EFEKTIVITAS MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP HASIL BELAJAR IPAS KELAS 5 SEKOLAH DASAR - Kumiati Wulandari; Syailin Nichla Choirin Attalina (LPPM Universitas Cipta Mandiri, 2024)
The study to aims evaluate the extent to which the snowball throwing learning model can improve the learning outcomes of IPAS grade 5 elementary school students, as well as to improve the understanding and application of IPAS material. The method used is a quantitative preexperimental approach with a one group pretest postest design. Researchers use test guideline that contain pretest postest questions and data analysis techniques using SPSS to find answer to problem formulation. The result of the study obtained an average pretest postest score of 66.29 and postest 83.39. in the t test obtained the result of t count 4.792> t table 2.042 so it can be said that the snowball throwing learning model is effective to be applied to be applied in grade 5 elementary school IPAS subjects.